Uncovering the Electron‐Phonon Interplay and Dynamical Energy‐Dissipation Mechanisms of Hot Carriers in Hybrid Lead Halide Perovskites. Issue 9 (27th January 2021) - Chan, Christopher C. S.; Fan, Kezhou; Wang, Han; Huang, Zhanfeng; Novko, Dino; Yan, Keyou; Xu, Jianbin; Choy, Wallace C. H.; Lončarić, Ivor; Wong, Kam Sing
Abstract: The discovery of slow hot carrier cooling in hybrid organic–inorganic lead halide perovskites (HOIPs) has provided exciting prospects for efficient solar cells that can overcome the Shockley–Queisser limit. Questions still loom over how electron‐phonon interactions differ from traditional polar semiconductors. Herein, the electron‐phonon coupling (EPC) strength of common perovskite films (MAPbBr3, MAPbI3, CsPbI3, and FAPbBr3 ) is obtained using transient absorption spectroscopy by analyzing the hot carrier cooling thermodynamics via a simplified two‐temperature model. Density function theory calculations are numerically performed at relevant electron‐temperatures to confirm experiments. Further, the variation of carrier‐temperature over a large range of carrier‐densities in HOIPs is analyzed, and an "S‐shaped" dependence of the initial carrier‐temperature to carrier‐density is reported. The phenomenon is attributed to the dominance of the large polaron screening and the destabilization effect which causes an increasing‐decreasing fluctuation in temperature at low excitation powers; and a hot‐phonon bottleneck which effectively increases the carrier temperature at higher carrier‐densities. The turning point in the relationship is indicative of the critical Mott density related to the nonmetal‐metal transition. The EPC analysis provides a novel perspective to quantify the energy transfer in HOIPs, electron‐lattice subsystem, and the complicated screening‐bottleneck interplay is comprehensively described, resolving the existing experimental contradictions. Abstract : The electron‐phonon coupling strength is quantified using a simplified two‐temperature model in several hybrid lead halide perovskites. Also, the intricate competition of hot‐carrier cooling mechanisms between large polaron screening and hot‐phonon bottleneck effect are described by unveiling an S‐shaped temperature versus carrier density relationship. The findings will help shed light on hot‐carrier harvesting in high‐performance photovoltaic applications.